Carnal resonance : affect and online pornography - Paasonen, Susanna, 1975- (Book collections on Project MUSE., 2011)
Here, Susanna Paasonen moves beyond the usual debates over the legal, political, and moral aspects of pornography to address online porn in a media historical framework, investigating its modalities, its affect, and its visceral and disturbing qualities.